Metabolic effects of goat milk yogurt supplemented with Smallanthus sonchifolius (yacon) root flour in rats on a high-fat diet - Grande, Maria Virginia (2019)
Overweight and obesity have increased dramatically in the world during recent decades, reaching epidemic levels. Currently, functional foods represent one of the most intensively investigated and widely promoted areas in the food and nutrition sciences in order to collaborate in obesity management. Yogurt is the most popular of fermented milks, rich in calcium and milk proteins with higher biological value and is an excellent delivery vehicle for functional ingredients such as fructooligosaccharides (FOS). Smallanthus sonchifolius (yacon) roots are considered the best natural source of FOS, and their consumption is associated with several health benefits. This study aimed to evaluate the effects of addition of yacon flour on the quality parameters of goat milk yogurt and investigate the metabolic effects of its regular consumption on high fat diet-fed Wistar rats. Yogurt was elaborated from goat milk and Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus, as starters and analyzed microbiologically weekly for a period of 30 days (shelf life of commercial yogurts). Yacon flour was added in a concentration of 7% (w/v). The centesimal composition of the product was determined. For the experimental model Wistar male rats (n=30) were divided into five groups (n=6 animal/group) receiving the specified diet: standard diet (Control); high fat diet (HFD); high fat diet plus yogurt (HFD-yogurt); high fat diet plus yacon flour (HFD-yacon); high fat diet plus yogurt + yacon (HFD-yogurt+yacon) during 30 days. The formulation containing yacon flour had higher nutritional values (fats 4%, proteins 4% and carbohydrates 6.74%) and improved sugar profile (reduced lactose 0.94% and increased prebiotic FOS 4.55%) content. The final product had acceptable sensory attributes and higher count (107 cfu/g) of viable probiotic microorganisms, with shelf life of at least 30 days. Supplementation of goat yogurt + yacon to a HFD resulted in a marked attenuation of weight gain and decrease in visceral fat pad weight (p<0.05). Moreover goat yogurt+yacon restored serum lipid profile, reduced fasting glucose levels, HOMA-IR, and atherogenic indices of rats, improving the effects of goat yogurt or yacon flour alone (p<0.05). Our results showed conclusive evidence indicating that goat yogurt + yacon is an excellent functional food that avoids the metabolic impact of high fat feeding, representing a novel food product for the management of obesity.